Rasch Typology Standard of Inventory Administration Practiced By Public Hospitals in Malaysia - Fariza Ahmad Mahyadin; Rohaizah Saad; Mohd Norhasni Mohd Asaad; Rushami Zien Yusoff (International Journal of Supply Chain Management, 2017)
This paper discussed on the major concern relating to the pharmacy department in hospitals which is facing difficulty in managing the drugs after investing in them and it is noted that by improperly taking care of the drugs, it will have an impact on the patients safety. The Rasch Measurement Model (RMM) with Winsteps Version 3.92.1 software was applied for data analysis due to its ability in interpreting and analyzing the ability of respondents in performing difficult items. Online questionnaires were distributed to selected public hospitals and out of 103 online questionnaires, 81 were returned with a response rate of 78.64%. However, only questionnaires from 80 respondents are useable. The typology standard result shows that the mean person of 3.01 and logit value of 2.02 differentiate the low competent and high competent hospitals into 51% and 49%. Easiest items (A1.4, A1.6 A1.10) and difficult items (A2.5 A2.6) have also been highlighted in the discussion. Public hospitals of S23 is the most competent while S51 is the lowest competent in implementing inventory administration. In addition, Rasch analysis points out that existing items need to be reviewed by adding more difficult items, in order to be developed further future research. Finally, this study is perhaps the first attempt in investigating the typology standard of inventory administration to be practised by public hospitals in Malaysia using RMM.